Microstructure and properties of cost-effective Fe–6.5 wt% Si ribbons fabricated by melt-spinning - Liang, Yongfeng; Wang, Shuai; Qi, Jiakun; Ye, Feng; Lin, Junpin (Scripta materialia, 2019)
Melt-spinning was successfully used to fabricate continuous Fe–6.5wt.%Si ribbons of 35 μm in thickness and 50–60 mm in width. Equiaxed grains measuring 2.4 ± 1.0 μm and columnar grains measuring 1.69 ± 0.72 μm were observed on the wheel and free surfaces, respectively. The as-spun ribbons showed strong 〈100〉 fiber texture, excellent room-temperature ductility, and very low core losses at high frequencies above 10 kHz. Compared with other fabricating techniques, the present work verified the feasibility for melt-spinning technique to fabricate ribbons of Fe–6.5 wt%Si with large-scale and thus cost-effective. [Display omitted]